Nexus between Monetary Freedom, Political Stability and Exchange Rate with Sustainable Stock Market Development in Pakistan: A Comparative Analysis by ARDL and NARDL - Islam, Kashif; Nasir, Nadia; Asghar, Nabila; Bilal, Ahmad Raza (Pakistan Journal of Humanities and Social Sciences, 2023)
This study scrutinizes both symmetric and asymmetric impact of monetary freedom (MF) on the sustainable stock market development (SMD) in Pakistan, in the presence of political stability and foreign exchange rate. The study uses the time series data for the period of 1992 to 2022, the study applies Non-linear Auto-regressive Distributed Lag (NARDL) and ARDL Bounds Testing for comparative analysis. Monetary freedom with sound political stability and stable foreign exchange rate do Granger Cause and significant correlation with the SMD of Pakistan. The results from ARDL Bound Testing show that MF and exchange rate has highly significant long-run impact on the SMD with coefficient values of 4.64 and 3.32. The Positive asymmetric cumulative dynamic multipliers (ACDMs) of MF have highly significant impact on SMD. Political stability has been a Positive Function of its ACDMs, while exchange rate has been a Negative Function of its respective ACDMs. The impact of exchange rate is highly significant with its Negative ACDMs coefficients of 17.42 and 16.76, denoting a long-lasting impact on the sustainable economic growth of Pakistan by strengthening the pace of stock market development. This comparative study will add revised practical credence to the existing literature on autoregressive models and will facilitate modified and improved policy-making at operational and strategic level to achieve decent economic growth under sustainable development goals (SDG).